Applied statistics for business and economics - Leekley, Robert M. (CRC Press, 2010)
Encourages development of application and decision making skills for use in managing raw data and real-world projects. This book includes such topics as scattergrams and time series graphs, simple and multiple regressions, time series analysis, and random sampling